Relationship between lower extremity stiffness and eccentric leg strength in horizontal jumpers - McMahon, J.; Graham-Smith, P. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Eccentric strength in the lower extremity has been identified as a key performance component in the horizontal jumps (Graham-Smith & Lees, 2005). Whilst isokinetic dynamometry provides a safe and reliable method of testing maximal eccentric strength, it is often criticised as being non functional due to testing at constant angular velocity and being an open kinetic chain movement (Baltzopoulos & Brodie, 1989; Augustsson & Thomeé, 2000). Therefore, eccentric leg strength measured during isokinetic testing may have limited transfer to functional performance. Lower extremity stiffness, such as vertical stiffness and knee joint stiffness (Farley et al., 1998) and knee joint moment, can be calculated during functional movements utilising force platforms, motion analysis and inverse dynamics. The purpose of this study was to examine the relationship between isokinetic eccentric leg strength and measures of lower extremity stiffness and knee joint moment during a single leg hop for distance test.